The Role of Siglec-G on Immune Cells in Sepsis - Royster, William; Wang, Ping; Aziz, Monowar (Frontiers in Immunology, 2021)
Sepsis is a life-threatening clinical syndrome that results from an overwhelming immune response to infection. During sepsis, immune cells are activated by sensing pathogen-associated molecular patterns and damage-associated molecular patterns (DAMPs) through pattern recognizing receptors (PRRs). Regulation of the immune response is essential to preventing or managing sepsis. Sialic acid-binding immunoglobulin-type lectin-G (Siglec-G), a CD33 group of Siglec expressed in B-1a cells and other hematopoietic cells, plays an important immunoregulatory role. B-1a cells, a subtype of B lymphocytes, spontaneously produce natural IgM which confers protection against infection. B-1a cells also produce IL-10, GM-CSF, and IL-35 to control inflammation. Sialic acids are present on cell membranes, receptors, and glycoproteins. Siglec-G binds to the sialic acid residues on the B cell receptor (BCR) and controls BCR-mediated signal transduction, thereby maintaining homeostasis of Ca++ influx and NFATc1 expression. Siglec-G inhibits NF-κB activation in B-1a cells and regulates B-1a cell proliferation. In myeloid cells, Siglec-G inhibits DAMP-mediated inflammation by forming a ternary complex with DAMP and CD24. Thus, preserving Siglec-G’s function could be a novel therapeutic approach in sepsis. Here, we review the immunoregulatory functions of Siglec-G in B-1a cells and myeloid cells in sepsis. A clear understanding of Siglec-G is important to developing novel therapeutics in treating sepsis.